Representasi Budaya Lokal Melalui Komunikasi Nonverbal Video Youtube Li Ziqi Tahun 2019-2021 - Gabriella Novenna Varra Manuputty (LPPM Stikosa-AWS, 2022)
Nonverbal communication is a symbol of strengthening the meaning of the message conveyed. The symbols usage found in intercultural communication can represent culture. This study researched using the descriptive analysis method that explains the study analysis of nonverbal communication theory by Larry A. Samovar and Richard E. Porter to interpret local cultural representations on several scenes taken from Li Ziqi's video as physical appearance; the concept of time; silence; haptic; paralanguage; proxemics; body position and foot position; costume; posture and spatial arrangement; and the last one is expression. The conclusion of the research using this theory is that nonverbal communication in Li Ziqi's video can communicate messages in the form of representations of local Chinese culture to audiences around the world with different cultural backgrounds. Li Ziqi's phenomenal video illustrates the importance of nonverbal communication in reading diverse intercultural communication.